User Driven Development: METAL as an Integrated Multilingual System - Schneider, Thomas (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractThe METAL machine translation system originally evolved from a cooperative effort with the University of Texas. After ten years of development, it became a product, intended to serve as a tool for the professional translator. The system is integrated into an office environment, incorporating processes like the automatic deformatting and reformatting of documents and interfaces to various word processing and desk top publishing systems. Recursive grammars and linguistic parallel processing plus a flexible lexicon structure lead to adequate translation quality. Experiences from some twenty installations, while very positive, have pointed out the need for further development beyond the purely linguistic: simplification of the user interface, higher error tolerance and integration with additional tools. Therefore, recent changes in the system have added components like pattern matching, version control, terminology and style checking, automated accounting and interfaces to a terminology data base. Both internal structure and user environment will be described.